2018
DOI: 10.1021/acs.jpca.8b04943
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on Hydrogen Abstraction by NO2 from Symmetric Ethers (CH3)2xO (x = 1–4)

Abstract: Hydrogen abstractions by NO from symmetric ethers are investigated to determine the rate constants and explore the effect of the functional group on rate constants at different reaction sites. The involved ethers are dimethyl ether (DME), diethyl ether (DEE), dipropyl ether (DPE), and dibutyl ether (DBE). The B3LYP method with a 6-31G(2df,p) basis set is employed to optimize the ground-state geometries and for frequency and intrinsic reaction coordinate calculations. The G4 method is used to calculate the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The model by Thion et al anticipates an even stronger reactivity enhancement, with the δ channel being more important than the γ channel. The recent theoretical work from Shang et al showed similar trends in the branching ratios for the abstraction reactions of dialkyl ethers by NO 2 . Interestingly, the SAR approach, as shown by the dotted lines in Figure , performs remarkably well in predicting the branching ratios, though it is unable to capture the reactivity order previously mentioned for the secondary sites in DBE: α > γ > β.…”
Section: Results and Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The model by Thion et al anticipates an even stronger reactivity enhancement, with the δ channel being more important than the γ channel. The recent theoretical work from Shang et al showed similar trends in the branching ratios for the abstraction reactions of dialkyl ethers by NO 2 . Interestingly, the SAR approach, as shown by the dotted lines in Figure , performs remarkably well in predicting the branching ratios, though it is unable to capture the reactivity order previously mentioned for the secondary sites in DBE: α > γ > β.…”
Section: Results and Discussionmentioning
confidence: 69%
“… a The data are compiled from Luo, Zhou et al, Shang et al, Yang et al, Serinyel et al, Thion et al., and Cai et al …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the energies of TSs are much higher than that of reactants, the formation of RCs with well depths of <3 kcal mol −1 is not a dominant process, which can be neglected in the rate constant calculations. 43 Fig. 9 compares the calculated MP-CVT/SCT rate constants of different channels for the H-abstraction reactions DMA + NO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…DMA has two types of hydrogen atoms, and the H-abstraction reactions from DMA by NO 2 at N-site and C-site are denoted as R1 and R2, respectively. According to the available studies, 43,44 the H-abstraction reactions by NO 2 lead to three products, i.e., HNO 2 , cis-HONO, and trans-HONO, and these channels are denoted as Rxa, Rxb, and Rxc (x = 1 and 2), respectively. In addition, 7 different reaction channels are also identified in this work.…”
Section: Resultsmentioning
confidence: 99%